Network Analysis Combining Proteomics and Metabolomics Reveals New Insights Into Early Responses of Eucalyptus grandis During Rust Infection - Sekiya, Alline; Marques, Felipe Garbelini; Leite, Thiago Falda; Cataldi, Thais Regiani; de Moraes, Fabricio Edgar; Pinheiro, Ana Lúcia Mendes; Labate, Mônica Teresa Veneziano; Labate, Carlos Alberto (Frontiers in Plant Science, 2021)
Eucalyptus rust is caused by the biotrophic fungus, Austropuccinia psidii, which affects commercial plantations of Eucalyptus, a major raw material for the pulp and paper industry in Brazil. Aiming to uncover the molecular mechanisms involved in rust resistance and susceptibility in Eucalyptus grandis, we used epifluorescence microscopy to follow the fungus development inside the leaves of two contrasting half-sibling genotypes (rust-resistance and rust-susceptible), to determine the time-course for comparative metabolomic and proteomic analyses in plantlets artificially inoculated with rust. Within 24 hours of complete fungal invasion, a total of 709 plant metabolites showed that the rust-resistant genotype suppressed many metabolites 6 hours after inoculation (hai), with responses being progressively induced after 12 hai. In contrast, the rust-susceptible genotype displayed an alternated metabolite response to infection, which culminated in a strong suppression at 24 hai. Multivariate analyses of genotypes and time points were used to select 16 differential metabolites chemically classified as flavonoids, benzenoids and other compounds. Applying the Weighted Gene Co-Expression Network Analysis (WGCNA), rust-resistant and rust-susceptible genotypes had, respectively, 871 and 852 proteins grouped into 14 and 13 modules, of which 10 and 7 protein modules were significantly correlated to the selected metabolites. Functional analyses revealed roles for oxidative-dependent responses leading to temporal activity of metabolites and proteins after 12 hai in rust-resistance, while the initial over-accumulation of metabolites and correlated proteins caused a lack of progressive response after 12 hai in rust-susceptible genotype. This study provides a brief understand on the temporal divergences of resistant and susceptible molecular responses of E. grandis plants to rust. Data are available via ProteomeXchange with identifier PXD021280.